Nigeria : 2012 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
The overarching policy challenge facing Nigeria is to reduce widespread poverty and unemployment. Macroeconomic performance was broadly positive, underpinned by buoyant international oil prices and prudent fiscal and monetary policies. The fiscal targets and the medium-term fiscal consolidation plan are consistent with supporting macroeconomic stability and creating fiscal space for much needed additional investment and social spending. Non-oil revenues need to be mobilized by moving quickly to improve tax administration in line with technical assistance (TA) recommendations. Planned structural reforms can substantially boost prospects for inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet